2020
DOI: 10.1017/s0142716420000296
|View full text |Cite
|
Sign up to set email alerts
|

The processing of multiword expressions in children and adults: An eye-tracking study of Chinese

Abstract: The processing advantage for multiword expressions over novel language has long been attested in the literature. However, the evidence pertains almost exclusively to multiword expression processing in adults. Whether or not other populations are sensitive to phrase frequency effects is largely unknown. Here, we sought to address this gap by recording the eye movements of third and fourth graders, as well as adults (first-language Mandarin) as they read phrases varying in frequency embedded in sentence context.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
51
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(66 citation statements)
references
References 82 publications
11
51
2
Order By: Relevance
“…Although children showed a similar downward trend of FL advantage across original and modified forms as adults did, the magnitude of the processing advantage was found to be larger in adults than in children. This finding is in line with existing research (e.g., Hallin & Van Lancker, 2017;Jiang et al, 2020). Compared with L1 adults, children had relatively limited exposure to target FSs, which decreased their sensitivity to FL in its original and modified forms.…”
Section: The Processing Of Modified Formulaic Language Vs Novel Language In Childrensupporting
confidence: 91%
See 1 more Smart Citation
“…Although children showed a similar downward trend of FL advantage across original and modified forms as adults did, the magnitude of the processing advantage was found to be larger in adults than in children. This finding is in line with existing research (e.g., Hallin & Van Lancker, 2017;Jiang et al, 2020). Compared with L1 adults, children had relatively limited exposure to target FSs, which decreased their sensitivity to FL in its original and modified forms.…”
Section: The Processing Of Modified Formulaic Language Vs Novel Language In Childrensupporting
confidence: 91%
“…For L1 children, as their age increased, the magnitude of the processing advantage increased. This finding is not surprising (e.g., Bannard & Matthews, 2008;Jiang et al, 2020). However, this was not the case in L2 adults.…”
Section: The Processing Of Modified Formulaic Language Vs Novel Language In Childrenmentioning
confidence: 81%
“…Besides, although studies on formulaic language processing have proliferated recently, most of them have focused on adults, with children being largely disregarded. Given that formulaic language plays an important role in first language (L1) acquisition and development (e.g., Clark, 1974;Lieven, Behrens, Speares, & Tomasello, 2003;Nelson, 1973;Peters, 1977), a better understanding of how it is processed by children is urgently needed (e.g., Jiang, Jiang, & Siyanova-Chanturia, 2020;Wray, 2002).…”
Section: List Of Tablesmentioning
confidence: 99%
“…Other researchers examined phrase frequency both as a categorical and a continuous variable in the data analysis (e.g., Arnon & Snider, 2010;Jiang, Jiang, & Siyanova-Chanturia, 2020;Northbrook & Conklin, 2019;Shantz, 2017;Siyanova-Chanturia et al, 2011b;Siyanova-Chanturia & Janssen, 2018;Wolter & Gyllstad, 2013). Some studies found the effect of phrase frequency was significant when it was treated as a continuous, not categorical, variable (e.g., Arnon & Snider, 2010;Shantz, 2017;Siyanova-Chanturia & Janssen, 2018).…”
Section: Frequencymentioning
confidence: 99%
See 1 more Smart Citation